2011
DOI: 10.1177/1043454211409582
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory of the Process of Adherence to Oral Chemotherapy in Hispanic and Caucasian Children and Adolescents With Acute Lymphoblastic Leukemia

Abstract: Children and adolescents with acute lymphoblastic leukemia (A.L.L.) receive treatment that relies on daily self- or parent/caregiver-administered oral chemotherapy for approximately two years. Despite the fact that pediatric A.L.L. is uniformly fatal without adequate treatment, non-adherence to oral chemotherapy has been observed in up to one-third of patients. Little is known about the reasons for non-adherence in these patients. This study employed Straussian grounded theory methodology to develop and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 67 publications
2
60
0
6
Order By: Relevance
“…However, findings on associations between treatment-related variables (ie, treatment modality, complexity, and duration; adverse impact on daily living) and adherence outcomes in pediatric cancer are mixed (Butow et al, 2010; Pritchard et al, 2006; Tamaroff, Festa, Adesman, & Walco, 1992). Studies with adolescents with cancer have reported forgetting to take medication as a leading reason for nonadherence (Hawwa et al, 2009; Landier et al, 2011; Mancini et al, 2012), which is also well documented in the broader adolescent chronic illness literature (La Greca & Mackey, 2009). Modifiable psychosocial patient-level associates, including higher depression and lower self-esteem, have also been found to relate to nonadherence in adolescents with cancer (Kennard et al, 2004; Malbasa et al, 2007; Tebbi et al, 1986).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…However, findings on associations between treatment-related variables (ie, treatment modality, complexity, and duration; adverse impact on daily living) and adherence outcomes in pediatric cancer are mixed (Butow et al, 2010; Pritchard et al, 2006; Tamaroff, Festa, Adesman, & Walco, 1992). Studies with adolescents with cancer have reported forgetting to take medication as a leading reason for nonadherence (Hawwa et al, 2009; Landier et al, 2011; Mancini et al, 2012), which is also well documented in the broader adolescent chronic illness literature (La Greca & Mackey, 2009). Modifiable psychosocial patient-level associates, including higher depression and lower self-esteem, have also been found to relate to nonadherence in adolescents with cancer (Kennard et al, 2004; Malbasa et al, 2007; Tebbi et al, 1986).…”
mentioning
confidence: 81%
“…Their model emphasizes the role of the parent, in conjunction with the child, in taking responsibility for medication adherence. To be successful, the following must be present: recognition of life threat, ability to take control, and ability to manage adherence consistently (Landier et al, 2011). Our study is informed by this model in that we examine both parent and child perspectives on adherence and related associates, with the aim to better understand how adolescents can maintain adherence long term.…”
mentioning
confidence: 99%
“…31,32 Improving AYA Adherence A recent qualitative investigation among AYA oncology patients described a ''process of adherence'' consisting of three distinct steps. 33 To adhere to a treatment regimen, patients must: (1) recognize the threat to long-term health and well-being posed by their cancer diagnosis, (2) take control of their treatment, and (3) manage it for the duration of therapy and survivorship. Less adherent behaviors may manifest if any or all of these steps are bypassed.…”
Section: Aya Developmental Challengesmentioning
confidence: 99%
“…The literature relies upon qualitative studies, often with small sample sizes involving questionnaires and in-depth interviews, and systematic reviews regarding the reasons of nonadherence, some of which present complex models of nonadherence [67,68]. Those in the field of hematology [69,70] may afford a unique insight into these diseases, and multicomponent tools can enable an integrated assessment of risk of nonadherence [71,72]. One qualitative study of 6 AYA patients under maintenance therapy for ALL identified 4 critical elements affecting adherence: a desire for normalcy, egocentrism, concrete thinking and parental involvement [73].…”
Section: Adolescents and Young Adultsmentioning
confidence: 99%